Keterlibatan Ayah dalam Pengasuhan pada Perkembangan Psikologi Anak : Studi Kasus Di Kota Jayapura - M. Musyafa’; Fauziyah Malik; Muhammad Hanif Rumaday (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study aims to examine the influence of father involvement in parenting on children's psychological development, focusing on the socio-cultural context of Jayapura City. In a society still influenced by patriarchal values, a father's role is often limited to economic functions, while emotional and affective involvement is still considered the mother's domain. This research used a qualitative approach with a case study method, involving in-depth interviews and participant observation with several families living in Jayapura City. The results indicate that a father's active involvement, whether in learning activities, emotional communication, or spiritual support, has a significant positive impact on children's self-confidence, emotional regulation, and stability of daily behavior. Conversely, low involvement tends to trigger emotional distance and psychological tension in children. Social, cultural, and communication style factors also influence the form and level of a father's involvement. These findings emphasize the importance of educating children about the role of fathers in parenting, as well as the need for a contextual and adaptive family counseling approach that aligns with local values ??in Jayapura City.